NF-Y is necessary for hematopoietic stem cell proliferation and survival - Bungartz, Gerd (American Society of Hematology, 2012)
HSC function depends on the tight control of proliferation and the balance between self-renewal and differentiation. Here, we report that the trimeric transcription factor NF-Y is critical for the survival of cycling, but not quiescent HSCs. With the use of a conditional knockout mouse model, we demonstrate that NF-Ya deletion creates an accumulation of HSCs in G(2)/M and prompts apoptosis, causing hematopoietic failure and death of the animal. These defects are accompanied by the dysregulation of multiple genes that influence cell cycle control (cyclin b1 and p21), apoptosis (Bcl-2), and self-renewal (HoxB4, Notch1, Bmi-1) and are independent of p53. Our results identify NF-Y as a pivotal upstream participant in a regu-latory network necessary for the pre-servation of cycling HSCs.